Alcoholics Anonymous Meetings for Teaching Sociology - Schwartz, T. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
During the past 15 years, I have learned to use open meetings of Alcoholics Anonymous (AA) to help me teach a wide array of topics including symbolic interaction, norms, rules, roles, belief systems, deviance, resocialization, subcultures, small groups, organizations, stratification, and research techniques in my courses in social psychology, introductory sociology, social problems, deviant behavior, criminology, and organizations. The meetings also provide excellent case studies with which to compare and contrast different theories in sociology and other disciplines. Students become more interested in people outside their own cohorts and in social and personal issues about substance abuse. As a result, most students seem to agree that all they could see at first was "a lot of miserable people" at the meetings, but by the end of the course they could see the meetings as fascinating social dramas and as opportunities to apply many of the sociological concepts and theories from the course.